Prebreeding and genetic enhancement of cultivated sunflower (Helianthus annuus L.) using diploid wild Helianthus species in India: Prebreeding and genetic enhancement of cultivated sunflower (Helianthus annuus L.) using diploid wild Helianthus species in India - H P MEENA; M SUJATHA; P S SRINIVAS; PRADUMAN YADAV (Journal of Oilseeds Research, 2023)
Pre-breeding activities using promising diploid wild Helianthus like Helianthus annuus (wild), H. argophyllus, H. praecox, H. debilis and H. petiolaris and popular cultivar (ARM-243B) have been initiated at ICAR Indian Institute of Oilseeds Research, Rajendranagar, Hyderabad to increase the frequency of desirable genes, wider adaptability and a broad genetic base. Wider variability was observed for yield and yield contributing traits besides disease reactions within and between species. Evaluation of a few populations for biotic stresses and yield related traits resulted in the identification of desirable introgression lines. The highest seed yield (42.5 g/plant) was reported in combinations with H. annuus (wild), H. petiolaris (40.2 g/plant) and H. debilis (39.8 g/plant). Interspecific derivatives derived from H. praecox were found resistant to powdery mildew. Interspecific derivatives of H. argophyllus, namely PB-1001, PB-1003, PB-1005, PB-1007, PB-1008, PB-1014, and PB-1019 were resistant to leafhoppers, while PB-1003, PB-1005, and PB-1007 exhibited resistant reactions to downy mildew under sick plot conditions. H. debilis derivatives viz., PB-120, PB-127, PB-128, PB-129 and PB-130 recorded >40% oil content. The pre-breeding lines derived from these interspecific cross combinations serve as an invaluable reservoir of genes for carrying out basic studies on the key traits as well as the exploitation of agronomically desirable traits in the AICRP sunflower breeding programmes.